KAJIAN NORMATIF PENERAPAN PIDANA MATI BAGI KORUPTOR DANA PENANGGULANGAN COVID-19 - Soren, Simon Maurits; Soleh, Moh. (Mimbar Keadilan, 2022)
Various positive responses and government efforts in overcoming the impacts caused by the Covid-19 pandemic in various aspects of the field. The status of the Covid-19 outbreak in Indonesia itself has been determined through Presidential Decree Number 11 of 2020 concerning the Determination of Public Health Emergency of Corona Virus Disease 2019 (Covid-19) and Presidential Decree Number 12 of 2020 concerning Determination of Non-natural Disasters for the Spread of Corona Virus Disease 2019 (Covid-19) as a National Disaster. However, the process of distributing social assistance by the government experienced various obstacles or the heavy disbursement of funds during the pandemic made the Corruption Eradication Commission act quickly in arresting several persons who misappropriated funds. Corruption committed during the Covid-19 pandemic emergency (non-natural disaster) is very detrimental and must be held criminally responsible for its actions. Therefore, it is important to know whether criminal responsibility for corruption perpetrators of social assistance during this pandemic has a deterrent effect or not. Considering that the Covid-19 emergency period has been designated by the government as a national disaster so that it fulfills the requirements for the phrase 'certain circumstances' contained in Article 2 paragraph 2 of Law Number 31 of 1999. This study uses a normative juridical method, namely examining laws and regulations, theory and legal concepts. The results of this study are to find out whether perpetrators of corruption during the Covid-19 period can be sentenced to prison and fines or even the death penalty.